A CPRBM-based method for large-deflection analysis of contact-aided compliant mechanisms considering beam-to-beam contacts. (March 2020) - Jin, Mohui; Zhu, Benliang; Mo, Jiasi; Yang, Zhou; Zhang, Xianmin; Howell, Larry L.
Highlights: An analysis method is proposed for contact-aided compliant mechanisms (CCMs). An approximation is proposed to determine the moving boundary of contact. The chained pseudo-rigid-body model is used to evaluate deformation and stress. The proposed method is straightforward. Abstract: Contact-aided compliant mechanisms (CCMs) utilize contact to achieve enhanced functionality. The contact phenomenon of CCMs increases the difficulties of their analysis and design, especially when they exhibit beam-to-beam contact. Considering the particularity of CCMs analysis, which is more about the mechanisms' deformation, this paper presents a numerical method to analyze the large deflection and stress of the CCMs considering beam-to-beam contacts. Based on our previous work on beam-to-rigid contact, the large deformation of general beams in CCMs is modeled by using the chained pseudo-rigid-body model (CPRBM). An approximation based on the geometric information of CPRBM is proposed in this paper to rapidly determine the moving boundary curve for beam-to-beam contact constraints. The static equilibrium configuration of CCMs is solved by minimizing its potential energy function under the geometric constraints from the boundary curves of contacts. A formulation is also provided to evaluate the normal stress along the deformed beam based on the deformation of CPRBM's torsional springs. Numerical examples and finite element analysis are used to verify the feasibility and accuracy of the proposed method.